Selective wheat germ agglutinin (WGA) uptake in the hippocampus from the locus coeruleus of dopamine-β-hydroxylase-WGA transgenic mice - Walling, Susan G; Brown, Robert A.; MIYASAKA, Nobuhiko; Yoshihara, Yoshihiro; Harley, Carolyn W. (Frontiers in Behavioral Neuroscience, 2012)
We generated transgenic mice in which a transsynaptic tracer, wheat germ agglutinin (WGA), was specifically expressed in the locus coeruleus neurons under the control of the dopamine-β-hydroxylase gene promoter. WGA protein was produced in more than 95% of the tyrosine hydroxylase-positive locus coeruleus neurons sampled. Transynaptic transfer of WGA was most evident in CA3 neurons of the hippocampus, but appeared absent in CA1 neurons. Faint but significant WGA immunoreactivity was observed surrounding the nuclei of dentate granule cells. Putative hilar mossy cells, identified by the presence of calretinin in the ventral hippocampus, appeared uniformly positive for transynaptically transferred WGA protein. GAD67-positive interneurons in the hilar and CA3 regions tended to be WGA-positive, although a subset of them did not show WGA co-localization. The same mixed WGA uptake profile was apparent when examining co-localization with parvalbumin. The selective uptake of WGA by dentate granule cells, mossy cells and CA3 pyramidal neurons is consistent with evidence for a large proportion of conventional synapses adjacent to locus coeruleus axonal varicosities in these regions. The lack of WGA uptake in the CA1 region and its relatively sparse innervation by dopamine-β-hydroxylase-positive fibers suggest that a majority of the tyrosine hydroxylase-positive classical synapses revealed by electron microscopy in that region may be producing dopamine. The overall pattern of WGA uptake in these transgenic mice suggests a selective role for the granule cell-mossy cell-CA3 network in processing novelty or the salient environmental contingency changes signaled by locus coeruleus activity.